Incidence and Impact of Various Complications on Pregnancy Related Anxiety in Women Attending an Obstetrics Clinic in a Tertiary Care Hospital - A, Srinivasan; Thambi, Smitha Sarah; D, Krishnarajan; KC, Arul Prakasam (Indian Journal of Pharmacy Practice)
Background: Pregnancy itself is associated with a slight percentage of risk. The presence of any complication can worsen it. Objectives: The study aimed to check the incidence and impact of various complications on pregnancy-related anxiety. Methods: This was a prospective observational study. All pregnant women irrespective of gestational weeks were included in the study. The anxiety levels of all pregnant women were checked using PRAQ-R2. A total of 212 women enrolled for the study but 12 women backed off due to incomplete data and finally 200 pregnant women attending an OBG clinic in a Tertiary care hospital were included in the study. The anxiety level scores of both pregnant women without any complication and those with complication was studied and compared. Correlation and significance were checked statistically. Results: The incidence of complications in pregnancy was 46%. The most common complication seen among the study population was thyroid problem. Pregnant women having some kind of complications showed a slightly higher score of anxiety when compared to women who didn't have any complications. Pregnant women with a wheezing problem, thyroid problem and PIH showed moderate levels of anxiety while pregnant women with other complications showed mild anxiety level. Pregnant women having twins showed a moderate level of anxiety. Conclusion: Age and parity of pregnancy had a significant effect on anxiety which was also proved statistically. Pregnant women having complications have slightly more levels of anxiety when compared to pregnant women who didn't have any complications along with present pregnancy.
Keywords: Pregnancy; Complications in pregnancy; Pregnancy-related anxiety; PRAQ-R2.